(untitled) (Perspectivas em Ciência da Informação, 2009)
The Scientometrics was used to analyze the literature regarding Health Sciences and Allied Health sciences by Portal de Periódicos da CAPES, aiming at providing subsidies to the alignment of Public Policies for S&T, literature features outlining, and the production of teaching material to bibliographic searches. It was concluded that there is an excessie amount of scientific journals duplicated, the national literature is meaningless or underrepresented, disproportion among the amount of the titles subscribed in each subject, insufficiency of titles in some areas; and also the incapacity of Qualis/CAPES System to classify scientific journals.